Improving Narrative Writing Skills Using the CIRC-Based Guided Writing Method: Empirical Evidence in Elementary School Environment - Nia A'isyah Septiarini; Panca Dewi Purwati (JOLLT Journal of Languages and Language Teaching, 2026)
Indonesia's 71st ranking among 81 countries in the 2022 PISA assessment highlights persistent challenges in foundational literacy, particularly in writing, where elementary students struggle with organizing ideas coherently, constructing engaging narratives, and demonstrating creativity. Although writing proficiency is essential for academic success, no studies have systematically combined Guided Writing and Cooperative Integrated Reading and Composition (CIRC) to develop narrative writing skills and creativity among early elementary learners. This study aimed to investigate the effectiveness of integrating Guided Writing with CIRC compared to the Think Talk Write (TTW) model in enhancing narrative writing skills and creative attitudes among third-grade students. A quasi-experimental non-equivalent control group design was employed involving 52 third-grade students from two public elementary schools in Tegowanu, Grobogan Regency. The experimental group (n=35) received CIRC-based instruction, while the control group (n=17) used the TTW model. Data were collected using a narrative writing assessment rubric and a creative attitude scale, then analyzed through independent samples t-tests. Results demonstrated that the CIRC approach significantly outperformed TTW in both measures, with experimental students achieving higher narrative writing scores (M=84.71 vs. M=73.24, p<0.001) and creative attitude scores (M=81.00 vs. M=73.88, p<0.001). These findings confirm that integrating Guided Writing within CIRC's collaborative framework more effectively develops both technical writing proficiency and creative expression than TTW. Teachers of early elementary grades are encouraged to adopt this integrated approach as a structured pedagogical strategy for improving narrative writing outcomes.